PEMILIHAN DOSEN PEMBIMBING SKRIPSI TERBAIK MENGGUNAKAN METODE COMPOSITE PERFORMANCE INDEX (CPI) - Muryono, Tupan Tri; Wiranata, Ade Davy; Sudaryana, I Ketut; Irwansyah, Irwansyah (Infotech: Journal of Technology Information, 2022)
Lecturers are professional educators and scientists with the main task of transforming, developing, and disseminating science, technology, and art through education, research, and community service. The problem in this research is that the process of selecting the best thesis lecturer is still subjective without considering the criteria and weighting factors and is also done manually resulting in the selection process being less effective and efficient. The method used in this research is the Composite Performance Index (CPI). Methods of data collection techniques by means of observation, interviews, documentation. From this research, the result is that the CPI method can help in selecting the best thesis supervisor and also the first rank is A6 with a value of 500, the second rank is A4 with a value of 470, and the third rank is A2 with a value of 445.